Pengaruh Pemberian Edukasi Tentang Anemia dan Penggunaan Kartu Kontrol Minum Tablet Tambah Darah (TTD) Terhadap Pengetahuan Ibu Hamil Di Wilayah Kerja Puskesmas Pakan Rabaa Kabupaten Lima Puluh Kota Tahun 2024 - Sonia Wulan Dari; Gita Ramadhani (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Anemia remains a significant issue during pregnancy. According to data from the Department of Health, Lima Puluh Kota District in 2022, out of 7,847 pregnant women, 1,362 (17.35%) were diagnosed with anemia. This study aims to determine the effect of education on anemia and the use of blood supplement tablet consumption control cards (TTD) on pregnant women's knowledge. This study used a pre-experimental design with a pretest and posttest one-group design. The research was conducted at Puskesmas Pakan Rabaa from October to November 2024. The population of the study consisted of all pregnant women in their first trimester in the working area of Puskesmas Pakan Rabaa from May to July, totaling 120 women, with a sample size of 32. Sampling was done using purposive sampling. After data collection, data were analyzed univariately and bivariately using paired t-test. The results showed that the average knowledge of pregnant women before the education on anemia and the use of blood supplement tablet consumption control cards was 14.78 with a standard deviation of 2.802, and after the education, it increased to 25.44 with a standard deviation of 2.961. The statistical test revealed a significant effect of education on anemia and the use of blood supplement tablet consumption control cards (TTD) on pregnant women's knowledge with a p-value of 0.000 (p < 0.05). The conclusion is that there is a significant effect of education on anemia and the use of blood supplement tablet consumption control cards (TTD) on pregnant women's knowledge. It is recommended that healthcare providers regularly deliver health education to enhance pregnant women's knowledge about anemia and the use of blood supplement tablet consumption control cards.